(untitled) (Sebha University Conference Proceedings, 2025)
Blades are the very important components of wind turbines in order to convert wind energy to mechanical or electrical energy. Therefore, the aerodynamic forces acting on the horizontal wind turbine blades have an important role in their performance. The objective of this paper is to investigate the aerodynamic characteristics and power generation properties for a NREL PHASE VI wind turbine blade. For this purpose, an analysis procedure based on the Blade Element Method (BEM) is demonstrated for a horizontal-axis wind turbine model (HAWT), and the methodology approach is discussed in detail throughout this paper. In this study, a Math Lab code has been developed for analyzing a model of Horizontal-Axis Wind Turbine (HAWT) in order to display aerodynamic behaviour on the blade. The NACA S809 airfoil was selected for the analysis of the wind turbine blade, where the tip and root losses proposed by Prandtl are also executed. The calculated results are validated using Q-Blade commercial software at rated wind speed of 10 m/s and show that the BEM is a good method of aerodynamic investigation of a HAWT blade